2022
DOI: 10.12968/jowc.2022.31.sup4.s10
|View full text |Cite
|
Sign up to set email alerts
|

Risk categorisation of patients attending a diabetic foot screening clinic in Suez

Abstract: Objective: To identify risk factors and assess diabetic foot ulcer (DFU) and amputation risk category (according to the 2015 International Working Group on the Diabetic Foot (IWGDF) guidance) among patients with type 2 diabetes in the Suez governorate, Egypt. Method: A cross-sectional study was conducted in the diabetic foot screening clinic of Suez General Hospital. A comprehensive sample of patients with type 2 diabetes attending the diabetes clinic every Saturday were enrolled in the study. Patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
2
Order By: Relevance
“…41 However, we report higher numbers of patients with low (36.7%) and moderate (36.1%) risk for diabetic foot were higher than reported in other studies. 37,41,42 For example, the proportion of participants with no risk of developing diabetic foot in our study was much lower than observed in comparative studies in other low-resourced countries e.g., 37.3% in Egypt, 42 57% in Kenyatta National Hospital, 41 and 72.7% in Tunisia. 37 The high proportion of patients with diabetes at high risk of developing diabetic foot in our study may be explained by several local reasons.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…41 However, we report higher numbers of patients with low (36.7%) and moderate (36.1%) risk for diabetic foot were higher than reported in other studies. 37,41,42 For example, the proportion of participants with no risk of developing diabetic foot in our study was much lower than observed in comparative studies in other low-resourced countries e.g., 37.3% in Egypt, 42 57% in Kenyatta National Hospital, 41 and 72.7% in Tunisia. 37 The high proportion of patients with diabetes at high risk of developing diabetic foot in our study may be explained by several local reasons.…”
Section: Discussioncontrasting
confidence: 83%
“…The diabetic foot risk classification has been proposed as an effective tool to prevent lower-extremity complications of diabetes and can form part of a screening system. 42,46 The proportion of participants with previous ulcers in our study was higher than in a recent study in Kenya where only 1.6% and 3.8% of patients had a history of or active foot ulcers, respectively. 8 This was, however, similar to previous studies in sub-Saharan Africa that reported 16% 41 and 4% to 61% 11,12 rates of previous foot ulceration.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation